Bevacizumab use and risk of cardiovascular adverse events among elderly patients with colorectal cancer receiving chemotherapy: a population-based study - Tsai, H.-T. (Oxford University Press, 2013)
BACKGROUND: Cardiovascular risk attributable to bevacizumab (Avastin(®), BEV) for treatment of metastatic colorectal cancer (CRC) remains unclear. We conducted a population-based cohort study to assess the safety of BEV use among patients aged ≥65. PATIENTS AND METHODS: We identified CRC patients diagnosed from 2005 to 2007 who received chemotherapy and were followed until 31 December 2009. Outcomes were 3-year risk of arterial thromboembolic events (ATEs), cardiomyopathy or congestive heart failure (CM/CHF), and cardiac death (CD) after chemotherapy initiation. We fitted Cox-proportional hazards (PHs) models with inverse-probability-of-treatment-weights and calculated hazard ratios (HRs) for the risk of adverse events. RESULTS: We identified 6803 CRC patients (median age: 73 years). Those with cardiac comorbidity were less likely to receive BEV (P < 0.0001). BEV is associated with an elevated risk of ATEs (HR = 1.82, 95% CI = 1.20–2.76, P < 0.001; rate difference: 3.5 additional cases/1000 person-years). We observed no association between BEV and CD or CM/CHF. CONCLUSIONS: In general practice, the cardiovascular risk of BEV in elderly CRC is modest. The observed ATEs risk is lower than reported in clinical trials, which may be due to careful patient selection. Our findings may facilitate clinical decision-making of BEV use in elderly patients.